Children’s Under the Age of 3 Transition from Home to Nursery: Exploring Greek Nursery Teachers’ Perspectives - Sotiropoulou, Eleni; Katsiada, Eleni; Berkovits, Anastasia (International Research in Education, 2022)
The purpose of this paper is to examine the perspectives of nursery teachers who work in Attica (Greece) about the transition of the children under the age of 3 from home to the nursery. The research was conducted with the quantitative sampling method, using a questionnaire with closed questions; a total of 195 educators were asked to answer a questionnaire using a five-point scale concerning the characteristics of children and the nursery environment which may affect the process of transition. In addition, the study examines whether the demographic characteristics of educators influence their views about transition. In summary, the aim of the study is to fill the existing research gap in Greece regarding the transition of children under the age of 3. The findings of this study suggest that nursery teachers place more emphasis on developing the emotional and social skills of children than skills related to language development and the ability to follow instructions. These findings are implications practitioners to further develop their nurseries transition programme.